2008
DOI: 10.1029/2008gl035516
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extreme, cold‐season synoptic precipitation events under global warming

Abstract: [1] We analyze regional climate model (RCM) simulations of daily, spatially distributed extreme precipitation events, using co-operative network observations and output from 10-year RCM simulations of present and future-scenario climates. We examine an Upper Mississippi River Basin region during October -March for daily amounts that exceed the 99.95th percentile and that occur simultaneously at several observation sites or model grid points. For the observations and each simulation, nearly all such extreme reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Resolution of each model within this region is listed on Table 2. This is the same region used in some of our previous precipitation analyses (Gutowski et al 2008(Gutowski et al , 2010Kawazoe and Gutowski 2013). Our analysis focuses on the winter season [December-February (DJF)], when synoptic dynamics are more important than in the warmer months, when smaller-scale convective events may be more important (e.g., Schumacher andJohnson 2005, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resolution of each model within this region is listed on Table 2. This is the same region used in some of our previous precipitation analyses (Gutowski et al 2008(Gutowski et al , 2010Kawazoe and Gutowski 2013). Our analysis focuses on the winter season [December-February (DJF)], when synoptic dynamics are more important than in the warmer months, when smaller-scale convective events may be more important (e.g., Schumacher andJohnson 2005, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis focuses on the winter season [December-February (DJF)], when synoptic dynamics are more important than in the warmer months, when smaller-scale convective events may be more important (e.g., Schumacher andJohnson 2005, 2006). This assumption here is that resolved circulation governs winter events, so that the other model fields we analyze are directly relevant to understanding the physical behavior of very heavy events (e.g., Gutowski et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested a strong increase in extreme precipitation over the south and central United States, but decreases over the Canadian prairies. Also, Gutowski et al (2008) showed that, for the Upper Mississippi River Basin region during October-March, the intensity of extreme precipitation is projected to increase.…”
Section: North Americamentioning
confidence: 99%
“…1: a coastal California (Coastal CA) region and an upper Mississippi River basin (Upper MS) region. Both regions have an annual maximum in net precipitation (precipitation 2 evaporation), and hence an accumulation of surface and subsurface water, during the cold half of the year (Gutowski et al 1997;Hamlet et al 2007;Tang et al 2010).…”
Section: Analysesmentioning
confidence: 99%